O saber empreendedor: diretrizes curriculares para elaboração de programas para formação de empreendedores com base na Escola Progressiva de John Dewey: reflexão e proposta - Ribas, Raul (2011)
This thesis aims to contribute to the state of the art for the area of education related to the formation of entrepreneurs. From a bibliographical and documentary, was select by hypothesis, the epistemological of Progressivism, developed by John Dewey through the conceptual analysis, proved to be more suitable for such programs. From the model resulting from the Experimental School of Progressivism, were developed curriculum guidelines for the training of entrepreneurs, independent of the activity of the origin of action taken. Based on these guidelines and in professional and academic experience of the author, was prepared to recommend a program for training of entrepreneurs, which detail the content and materials available, allows your application transcends the academic sphere, to also achieve a practical utility. This second possibility of applying this theory corresponds to the author s desire to contribute, beyond the theoretical aspects, to increase the chances of success for individuals who begin theirs initiatives to undertake